2015
DOI: 10.1128/cvi.00147-15
|View full text |Cite
|
Sign up to set email alerts
|

Normal Free Interleukin-18 (IL-18) Plasma Levels in Dengue Virus Infection and the Need To Measure Both Total IL-18 and IL-18 Binding Protein Levels

Abstract: bActivated monocytes/macrophages and T lymphocytes that produce a cytokine storm are assumed to play a pivotal role in the pathogenesis of dengue. Interleukin-18 (IL-18) is a proinflammatory cytokine that is increased during dengue and known to induce gamma interferon (IFN-␥), which is crucial for dengue immune response. No data are available regarding the balance between IL-18 and its natural inhibitor IL-18 binding protein (IL-18BP) and how they interact within the inflammatory reaction of patients with deng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…Interestingly, although IL-18BPa was elevated in our current cohort, the proportion of IL-18BPa to IL-18 was similar among controls and diabetics. This is consistent with other reports which demonstrate IL-18BP and IL-18 increasing and decreasing concordantly (54,55), except in unique pathologies (56). While a provocative finding, the elevation of IL-18BPa raises the questions of source and cause.…”
Section: Cytokinessupporting
confidence: 92%
“…Interestingly, although IL-18BPa was elevated in our current cohort, the proportion of IL-18BPa to IL-18 was similar among controls and diabetics. This is consistent with other reports which demonstrate IL-18BP and IL-18 increasing and decreasing concordantly (54,55), except in unique pathologies (56). While a provocative finding, the elevation of IL-18BPa raises the questions of source and cause.…”
Section: Cytokinessupporting
confidence: 92%
“…We found that although serum IL-18 levels were higher in patients with DHF compared to those with DF, especially during early illness, these differences were not significant at any time point ( Figure 3A). The median values of IL-18 seen throughout the course of illness was similar to the values observed previously in patients with DHF (median values 409.5 pg/ml in early illness to 352.3 pg/ml in late illness) and DF (median values 327.1 pg/ml in early illness to 224.2 pg/ml in late illness) ( Fig 3A)[28] and were several folds higher than IL-18 levels seen in healthy individuals [28]. However, serum IL-18 levels did show a statistically significant but weak correlation with serum LPS levels (Spearman's r=0.20, p=0.009) ( Figure 3B).…”
Section: Association Of Serum Il-18 and Lps In Patients With Acute Desupporting
confidence: 88%
“…For IG measurements – reported as percentage of total leukocyte count or as absolute numbers – the membranes of mature WBC were first partly lysed before analyzing light scatter properties and the nucleic acid content of the cells in the leukocyte differentiation channel. The laboratory confirmation of dengue, leptospirosis, and enteric fever diagnosis was made as previously described for this cohort .…”
Section: Methodsmentioning
confidence: 99%